2011
DOI: 10.2214/ajr.10.5342
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Masses in Patients With Cancer: PET/CT Characterization With Combined CT Histogram and Standardized Uptake Value PET Analysis

Abstract: The combination of SUV and CT histogram analysis allowed us to significantly improve the PET/CT diagnostic accuracy for characterizing adrenal lesions, leading to a significant reduction in the number of false-positive cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…The combination of unenhanced CT and SUV max ratio is highly accurate in distinguishing between benign and malignant adrenal lesions [25]. In our study, applying the suggested unenhanced attenuation and SUV max ratio cut-off values of 10 HU and 2.5, respectively, substantially increased the accuracy of the test and would have decreased the number of false-positive results.…”
Section: Discussionmentioning
confidence: 61%
“…The combination of unenhanced CT and SUV max ratio is highly accurate in distinguishing between benign and malignant adrenal lesions [25]. In our study, applying the suggested unenhanced attenuation and SUV max ratio cut-off values of 10 HU and 2.5, respectively, substantially increased the accuracy of the test and would have decreased the number of false-positive results.…”
Section: Discussionmentioning
confidence: 61%
“…In 325 patients with adrenal lesions, the highest accuracy, sensitivity (99 %) and specificity (91 %), was found when max SUV adrenal:liver ratio [2.5 was combined with HU [ 10 [44]. FDG PET/CT metabolic measurements have been combined with CT histogram and unenhanced CT parameters (Hounsfield units, size), SUV max[2.8 with histograms and Hounsfield units \20 with excellent results [45].…”
Section: Normal Adrenal Anatomy and Metabolic Featuresmentioning
confidence: 99%
“…6.4, 6.5) [25,26]. A more recent study found that the combination of 18-FDG PET/CT with standard uptake values (SUV) and CT histogram analysis further improves the diagnostic accuracy of adrenal lesions characterization, yielding a sensitivity of 100 % and specificity of 97.3 % [27].…”
Section: State Of the Art Conventional (Multi-detector) Ctmentioning
confidence: 99%